Case Report: Left bundle branch area pacing in cardiac resynchronization therapy increases conduction velocity - Zhang, Wenchang; Wang, Leyi; He, Changjian; Ding, Chunhua (Frontiers in Cardiovascular Medicine, 2025)
Several studies have suggested that the application of left bundle branch area pacing (LBBAP) in cardiac resynchronization therapy (CRT) holds promise as a treatment modality for correcting left bundle branch block (LBBB) while concurrently enhancing left ventricular structure and function. However, it's noteworthy that current guidelines do not provide specific recommendations for the use of left bundle branch area pacing, underscoring the need for additional evidence regarding its safety and efficacy. In this context, we present a case report detailing the utilization of LBBAP-CRTD treatment in a patient with LBBB-induced cardiomyopathy. The investigation encompasses a thorough examination of the efficacy and safety of LBBAP-CRTD, with a particular emphasis on cardiac synchronization parameters. Written consent was obtained from the patient, and this case report adheres to the CARE guideline.